THE EFFECT OF HEXAGON FRAUD ON FINANCIAL STATEMENT FRAUD (EMPIRICAL STUDY OF INFRASTRUCTURE SECTOR COMPANIES IN 2020-2022) - Mohamad Zulman Hakim; Dewi Rachmania; Indra Gunawan Siregar; Adela Rhiana Novitasari; Anggun Munifatul Afifah; Pika Yolanda (ZILLZELL MEDIA PRIMA, 2023)
Financial statement fraud is a discrepancy between the application of accounting principles and the preparation of financial statements with the aim of deceiving users of financial statements. This study aims to analyze the effect of Fraud Hexagon on fraudulent financial statements. There are 10 variables used, namely Financial Targets, Financial Stability, External Pressure, Monitoring, Ideal conditions of a company, the position of a CEO, Managerial Ownership, Change of directors, Government Ownership, Political connections. Financial statement fraud is measured using the Beneish M-Score Model. The sample in this research is infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021 with a total sample of 27 companies. data analysis in this study using panel data regression analysis. The results of this study indicate that the financial targets and ideal conditions of a company have an influence on the potential for fraudulent financial reporting. Financial Stability, External pressure, Monitoring, the position of a CEO, Managerial Ownership, Change of directors, Government Ownership, Political connections have no influence on the potential for fraudulent financial reporting.